Postmodernism and the Crisis of Trust in Government: An Analysis of Michel Foucault's Thought - Holivil, Ernestus; Wulakada, Hamza H.; Gasa, Frederik Masri; Long, Belandina Liliana (Jurnal Filsafat "WISDOM", 2025)
This study aims to analyze the causes of the crisis of trust in government from a postmodernist perspective, referring to Michel Foucault's concepts of governmentality and biopolitics. The central research question explores how power, as expressed through public policy discourse, can impact government legitimacy, particularly during global crises. A qualitative approach is used, employing critical philosophical analysis of Foucault's texts, with case studies on pandemic policies and the use of surveillance technology. The findings reveal that the decline in public trust is not only due to administrative failures but also due to the way governments manage policy discourse in ways that are opaque and manipulative. Based on these findings, the study suggests that governments should adopt more transparent and participatory policy approaches, increasing public involvement in decision-making processes to strengthen the legitimacy of the government, which has been undermined.